2004
DOI: 10.1080/02724990344000169
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of generalization decrement in causal learning

Abstract: Two experiments required volunteers to learn which of various "planes" caused high levels of pollution. Novel test items were then rated as causes of pollution. Items created by adding novel features were rated at the same level as that of the original training items but items created by removing features received reduced ratings. This asymmetry of generalization decrement was not predicted by a well-known configural model of stimulus representation (Pearce, 1987, 1994) but was predicted by a recently proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 22 publications
5
34
3
Order By: Relevance
“…Up to now, studies that have investigated generalization decrement explicitly have routinely observed asymmetrical generalization decrements (Brandon, Vogel, & Wagner, 2000;Glautier, 2004;González, Quinn, & Fanselow, 2003;Wheeler, Amundson, & Miller, 2006 Glautier's (2004) experiments, participants had to rate the amount of air pollution produced by airplanes. Stimuli created by adding novel features (such as markings or guns) to the previously trained airplanes were rated at the same level as the original training stimuli, but stimuli created by removing features led to reduced ratings.…”
Section: Methodsmentioning
confidence: 99%
“…Up to now, studies that have investigated generalization decrement explicitly have routinely observed asymmetrical generalization decrements (Brandon, Vogel, & Wagner, 2000;Glautier, 2004;González, Quinn, & Fanselow, 2003;Wheeler, Amundson, & Miller, 2006 Glautier's (2004) experiments, participants had to rate the amount of air pollution produced by airplanes. Stimuli created by adding novel features (such as markings or guns) to the previously trained airplanes were rated at the same level as the original training stimuli, but stimuli created by removing features led to reduced ratings.…”
Section: Methodsmentioning
confidence: 99%
“…It doesn't matter how fast you answer; therefore, take the time you need. If ies of Wheeler et al (2006) and Glautier (2004), which had observed asymmetrical decrements. Furthermore, this would be in line with the suggestion of Pineño et al (2005) that there is greater susceptibility to cue competition in causal than in predictive attribution.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, experiments intended to compare these decrements reported only asymmetrical decrements in human (Glautier, 2004;Wheeler et al, 2006), as well as in nonhuman learning (Brandon et al, 2000;González et al, 2003) 1 . Guided by the question "Under which conditions is processing best described by configural theories, and under which conditions is it best described by elemental theories?…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations